5.2.13-eg - k , starting with k = 0, so the entries in the...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Example (a) Find a function f ( k ) so that 3 + 6 + 9 + 12 = 4 X k =1 f ( k ) . (b) Find a function g ( k ) so that 3 + 6 + 9 + 12 = 3 X k =0 g ( k ) . Solution: (a) For the first summation the index of summation is k , starting with k = 1, the entries in the sum can be identified as follows 3 |{z} k =1 + 6 |{z} k =2 + 9 |{z} k =3 + 12 |{z} k =4 , so the formula for the k th term can be found by noting that 3 = 3 · k, for k = 1 , 6 = 3 · k, for k = 2 , 9 = 3 · k, for k = 3 , 12 = 3 · k, for k = 4 . Thus, f ( k ) = 3 k. (b) Here the index of summation is
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: k , starting with k = 0, so the entries in the sum can be identied as follows 3 |{z} k =0 + 6 |{z} k =1 + 9 |{z} k =2 + 12 |{z} k =3 . Writing each term as a function of k , 3 = 3 1 = 3 ( k + 1) , for k = 0 , 6 = 3 2 = 3 ( k + 1) , for k = 1 , 9 = 3 3 = 3 ( k + 1) , for k = 2 , 12 = 3 4 = 3 ( k + 1) , for k = 3 , Thus, g ( k ) = 3( k + 1) ....
View Full Document

This note was uploaded on 04/02/2012 for the course MTH 132 taught by Professor Kihyunhyun during the Fall '10 term at Michigan State University.

Ask a homework question - tutors are online